Implementation of The Tiered Supervision as a Supervision Function - Retno Wahyu Nugrahini; Vivi Yosafianti Pohan (University of Muhammadiyah Semarang, 2020)
Tiered supervision that supports improving the quality of nursing services in the field of nursing at Sultan Agung Islamic Hospital has not been carried out in a structured and documented manner. Baitul Izzah 1 room as a disease treatment room in class III, the head of the room has not yet supervised the Person in Charge of Care (PPJA) and so on PPJA to the Associate Nurse (PP). The supervision that has been carried out so far is only to ask directly about existing problems to the head of the room and directly observe the activities of implementing nursing care by PPJA and PP. Tiered supervision does not go well, because there are no references and standards for its implementation. The purpose of this study was to determine Implementation of The Tiered Supervision as a Supervision Function. It was found that the implementation of tiered supervision instruments improved the performance of the head of the room, PPJA and PP, then the patient's medical record document increases in completeness chargingespecially the patient's Islamic education document. In conclusion, tiered supervision instruments are very helpful in the implementation of the supervisory function as well as monitoring and evaluation in nursing management in the implementation of nursing care in the inpatient room. The recommendation for the role of the nursing field that is most important in controlling the quality of nursing care is to actively involve staff to jointly ensure the continuity of the implementation of tiered nursing supervision.